Evaluación de los factores de riesgos del trabajo y su incidencia en la seguridad y salud ocupacional en la universidad técnica de Cotopaxi del cantón Latacunga, 2015. Propuesta elaboración de la matriz de riesgos. - Bustos, Mauricio (2016)
The evaluation of risk factors and their impact on safety and occupational health at Technical University of Cotopaxi the research had as a main objective to understand the risks that workers, collaborators and teachers must face in the three faculties San Felipe, Salache, La Maná. The methodology used descriptive and quali - quantitative research, and a field research with a transverse approach; The process began with the observation actions that may create risks caused by collaborators to perform different activities and tasks, such as working conditions that they develop. Then risks were identified by the survey conducted for the purpose, and when the assessment of risks was developed according to the survey results of risks, it was obtained that generate the greatest impact on workers are: mechanical and ergonomic risks, on collaborators are ergonomic and psychosocial while for teachers are physical and ergonomic which have to be checked by the University in charged of it, to prevent the occurrence of accidents and occupational disease risks. To test the relationship between risk factors and these unwanted events, the X2 (chi square) test was used which resulted in there is significant relationship between these variables. Finally it was proposed the development of matrix risk with their respective intervention measures to improve the safety and occupational health.